Microscopic structure of the radiative centre in As2Se3 crystals - Ristein, Jürgen; et al. (Solid State Communications, 1988)
The dependence of the strongly Stokes shifted luminescence and of the photocurrent on the exciting light intensity points to the onset of bimolecular non radiative recombination of trapped geminate pairs at densities above 1018/cm3. Saturation of the luminescence is not observed which leads to the conclusion that excited pairs are self trapped by rapid lattice distortion. A microscopic model based on considerations of the chemical bonds and recent bandstructure calculations is proposed with the lattice distortion resulting from formation of an interlayer π bond involving Se lone pair states near an inversion centre. A precursor of the bond exists already in the ground state causing a small monoclinic distortion of the lattice and inequivalence of Se sites which in an isolated layer are related by mirror symmetry. © 1988.
UnivIS-Import:2015-03-05:Pub.1988.nat.dphy.IAP.exphys.micros